IgG4 prostatitis associated with prostatic adenocarcinoma: A case report and literature review - Shaun A.C. Medlicott, MD, FRCPC; Allan Oryschak, MD, FRCPC; Kiril Trpkov, MD, FRCPC (Elsevier, 2018)
A 66-year-old male patient had a prostate biopsy for an elevated serum prostate specific antigen which revealed prostatic adenocarcinoma, Gleason score 3 + 4 = 7 (Grade group 2) with marked background chronic inflammation. A radical prostatectomy showed prostatic adenocarcinoma accompanied by IgG4 prostatitis, which had not been appreciated in the biopsy. The patient had chronic asthma and 4 years prior to the biopsy he had been diagnosed with IgG4-related orbital disease. This history was however unknown during the initial interpretation of the prostate biopsy and prostatectomy. No autoimmune pancreatobiliary involvement was documented at any point, either initially or during the follow-up. IgG4-related prostatitis and prostatic adenocarcinoma have been previously reported to occur simultaneously only in 2 cases. We provide additional evidence that prostatic adenocarcinoma and IgG4-related disease may be found synchronously in the prostate. Therefore, it is important to consider the possibility of an unrecognized IgG4 prostatitis, whenever a heavy lymphoplasmacytic inflammation is found in the prostate, particularly in the absence of a marked granulomatous reaction. To our knowledge, IgG4 prostatitis and prostatic adenocarcinoma accompanied by orbital IgG4-related disease, but without a pancreatobiliary involvement, have not been previously documented. Keywords: IgG4-related disease, prostatitis, prostatic adenocarcinoma, IgG4-orbital disease, dacryoadenitis